Translational research in stroke - Lapchak, Paul A.; Yang, Guo-Yuan (Springer, 2018)
This book mainly discusses the current status of stroke transnational research and allows the reader to understand the interplay of common comorbidities in the stroke population such as diabetes and hypertension, and provides insight into stroke targets to promote cell survival, angiogenesis, neurogenesis, and most importantly, functional recovery after stroke. Throughout the world, stroke is still a leading cause of mortality and morbidity; each year approximately 15 million people worldwide suffer from stroke. Stroke is now the leading cause of death and disability in China. Large communities of stroke survivors are eagerly awaiting scientific advances in transnational stroke research that would offer neuroprotective therapeutics for acute stroke management, or rehabilitation and regenerative strategies utilizing novel stem cell-based approaches. While research is ongoing, the Editors have compiled this volume to help the further understanding of the pathophysiology of stroke and to review and identify future potential biomarkers. The book is written for students, researchers and physicians in neurosciences, neurology and neuroradiology.
Keywords: Cerebrovascular disease -- Research.; Medicine -- Research.; elektronické knihy; electronic books